Translational succession - A. S. Slipchenko (Bulletin of Kharkiv National University of Internal Affairs)
The article examines the translational succession. The characteristic features and signs of legal acquisition have been identified. The features of translative succession, modern and most common approaches to its understanding have been considered. A comparison of translative succession and constitutive succession has been made. By identifying such differences, the article outlines the boundaries of the concept of “translative succession”. The method of analysis, synthesis and comparison has been used in the work, which allowed to identify the structural components of succession and to bring them together.